Efektivitas Implementasi Kebijakan Izin Pendirian Bangunan Homestay Di Sempadan Pantai Klayar Kabupaten Pacitan - Silvananda Adping; I Gusti Ayu Ketut Rachmi Handayani; Rosita Candrakirana (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This research is an effort to describe and examine the problems, first regarding the Policy Arrangements for Homestay Building Permits on the Border of Klayar Beach, Pacitan Regency. Second, regarding the Effectiveness of Implementing the Permit Policy for the Establishment of Homestay Buildings on the Border of Klayar Beach, Pacitan Regency. The research method used is an empirical legal research method with a descriptive nature using a Sociology of Law approach. The results of the research show that there are problems that have not been resolved by Pacitan Regency in implementing the Homestay building permit policy on the Klayar Beach Border, Pacitan Regency, namely the absence of regulations within the Pacitan Regency area relating to specific arrangements regarding Homestay building permit procedures on the Beach Border. Therefore, the Regional Government needs to create a Building Approval (PBG) policy that can accommodate the interests of the community without ignoring environmental interests. Specifically related to building permit policies to realize the principle of ease in obtaining building permits.